2015
DOI: 10.1074/jbc.m114.614750
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted-in-schizophrenia 1 (DISC1) Regulates Dysbindin Function by Enhancing Its Stability

Abstract: Background: Dysbindin and Disrupted-in-schizophrenia 1 (DISC1) are major schizophrenia susceptibility factors. Results: DISC1 enhances stability of dysbindin, which is critical for neurite outgrowth. Conclusion: Dysbindin and DISC1 form a physiologically functional complex that is essential for normal neurite outgrowth. Significance: Our findings indicate the existence of a protein complex composed of multiple schizophrenia susceptibility factors functioning in a pathway for neurite outgrowth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…CAD cells were transfected with pmCherry-N1 (Clontech) and FITC-conjugated siRNAs targeting mouse REST or TRIM28 using Lipofectamine 2000 as described previously68. At 48 h post transfection, cells were detached and seeded again onto plates and then cultured for 48 h in serum-free DMEM media for differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…CAD cells were transfected with pmCherry-N1 (Clontech) and FITC-conjugated siRNAs targeting mouse REST or TRIM28 using Lipofectamine 2000 as described previously68. At 48 h post transfection, cells were detached and seeded again onto plates and then cultured for 48 h in serum-free DMEM media for differentiation.…”
Section: Methodsmentioning
confidence: 99%
“…DISC1 codes for a major protein of about 100 kDa and various, yet incompletely characterized isoforms generated by alternative splicing [26]. Many studies have demonstrated that DISC1 plays important roles during neurodevelopment, including neuronal proliferation, neurite outgrowth, neuronal migration, and synapse formation, all implicated in the pathophysiology of schizophrenia (reviewed in [27]). Furthermore, genetic variants of DISC1 were shown to be associated with the hippocampal volume [28], cortical thickness [29], and prefrontal-associated cognition [25].…”
Section: Introductionmentioning
confidence: 99%
“…; Lee et al . ) and regulates a large number of cellular processes including nuclear transcription (Fu et al . ), the activity of Calmodulin‐dependent Kinase (Papaleo et al .…”
mentioning
confidence: 99%